Efektivitas Larangan Merokok Terhadap Mahasiswa Fakultas Hukum UPN “Veteran” Jakarta Angkatan 2022 - Wulandari, Diah Ayu; Maniari, Elsa; Afifa, Erina Nur; Marito, Eugina Evita; Indiyarto, Fadhil Muhammad; Bakhtiar, Handar Subhandi (Media Hukum Indonesia (MHI), 2024)
The Smoke-Free Zone is one of the efforts made by the government to protect the community, including passive smokers, from the dangers of exposure to cigarette smoke. Teaching and learning places (schools and universities) are one of the areas that are included in the category of Non-Smoking Areas (KTR), as well as the UPN "Veteran" Jakarta Campus area. This is supported by the Rector's Regulation Number 11 of 2019 concerning the Prohibition of Smoking in the campus area. However, there are still many students who smoke in various corners of the campus when walking around the campus. This study aims to look at regulations related to the smoking ban in the UPN "Veteran" Jakarta campus environment and the effectiveness of the implementation of Rector's Regulation Number 11 of 2019 concerning Smoking Prohibition for law faculty students of the class of 2022. The method used is empirical legal research (sociolegal research) by looking at the actuality or reality of the application of law in society. The data collection technique is carried out through the distribution of questionnaires and using literature studies. This study uses Descriptive Statistical Techniques as a data analysis technique by describing or describing the data that has been collected without changing the original data results. The results of this study show that the existence of the Jakarta UPN "Veteran" Rector Regulation Number 11 of 2019 has not been implemented in an orderly and effective manner. This is because Law Students of the Class of 2022 are still found smoking around the Faculty of Law area and also the campus environment.